Peran Camat Dalam Meningkatkan Disiplin Pegawai Di Kantor Kecamatan Kabupaten Bandung - Priansyah, Noval (Jurnal Syntax Fusion, 2023)
The sub-district head plays a very important role in improving the discipline of his employees because the sub-district head as a leader must carry out his leadership well, so that all work can run smoothly and be completed on time. This study aims to determine the extent to which the Camat's role in improving employee discipline. explaining the thoughts taken by researchers is the role theory of Nadler (in Akbar, Page 159. 2018) the role is divided into 3 indicators namely: 1 Provisions, 2 Descriptions, 3 Expectations. Research using descriptive qualitative method that aims to provide an explanation of a problem by analyzing data to provide conclusions. To collect data, researchers used several data collection techniques including: Observation techniques, namely data collection techniques directly from the object of research. Interview techniques to collect clearer data according to research needs through interviewing several informants directly in the research area and conducting documentation and literature studies, after the research was carried out and analyzing the various data obtained, it can be concluded that the Role of the Camat in Improving Employee Discipline at the Pangalengan District Office Bandung district. Namely to assess the extent to which the Camat's Role as a Leader in improving the Discipline of Employees in the Pangalengan District Office, Bandung Regency. The conclusion is that the role of the Camat in Improving Employee Discipline in the Pangalengan District Office, Bandung Regency, namely: Although the Camat's time is limited, the Camat tries to provide a good role for employees in the Pangalengan District Office, Bandung Regency and provides motivation for employees.